Integrating 3D-printed PHBV/Calcium sulfate hemihydrate scaffold and chitosan hydrogel for enhanced osteogenic property. (15th December 2018) - Ye, Xiangling; Li, Lihua; Lin, Zefeng; Yang, Weiliang; Duan, Mingyang; Chen, Lingling; Xia, Yuanjun; Chen, Zepeng; Lu, Yao; Zhang, Ying
Highlights: Porous PHBV/CaSH scaffolds with good mechanical performance were 3D-printed using the fused deposition modeling technique. The PHBV/CaSH scaffolds were integrated with the chitosan hydrogel to fabricate the novel PHBV/CaSH/CS scaffolds. The PHBV/CaSH/CS scaffolds enhanced osteogensis of bone marrow stem cells, resulting in better bone formation in vivo . Abstract: We developed the 3D-printed poly(3-hydroxybutyrate-co-3-hydroxyvalerate)/calcium sulfate hemihydrate (PHBV/CaSH) scaffolds by using fused deposition modelling (FDM) technique and then coated the scaffolds with chitosan (CS) acetic acid solution. After drying and neutralization, CS hydrogel was formed on the surface of the scaffolds. The resultant PHBV/CaSH/CS scaffolds could promote the adhesion and proliferation of rat bone marrow stromal cells (rBMSCs) and enhance the osteogenesis of rBMSCs by up-regulating the expression level of osteogenic genes compared to the PHBV and PHBV/CaSH scaffolds. In vivo studies further demonstrated the PHBV/CaSH/CS scaffolds could effectively promote new bone formation. Therefore, integrating 3D-printed PHBV/CaSH scaffold and CS hrydogel represents a novel strategy to promote osteogensis property, showing full potential for bone defects repair.